The Influence of Professional Identity, Learning Motivation on Learning Engagement among Vocational Architecture Students - Kaijun Du; Krittavit Bhumithavara (Al-Qalam Institute, 2026)
Learning engagement has emerged as a central indicator of quality in higher education amid the growing emphasis on student-centered evaluation. This study aims to examine the influence of professional identity and learning motivation on learning engagement among vocational architecture students. A quantitative approach was employed involving 312 students selected through stratified random sampling. Data were collected using validated questionnaires that measured professional identity, intrinsic and extrinsic learning motivation, and learning engagement, and were then analyzed using structural equation modeling. The results indicate that professional identity significantly predicts learning engagement (β = 0.41, p < 0.001), while intrinsic motivation shows a stronger effect (β = 0.46, p < 0.001) than extrinsic motivation (β = 0.18, p < 0.05). Together, the variables explain 62% of the variance in learning engagement. This study contributes to understanding the internal psychological determinants of engagement in vocational education. The findings suggest strengthening professional identity formation and fostering intrinsic motivation to enhance student engagement.